Effect of rice wastewater poc and planting distance on growth and yield of green Mung Beans (Vigna Radiata L.) - Pratama, Mikdad Mulya; Respati, Laras Laksita; Faqih, Achmad (International Journal Labs, 2024)
This study aims to determine the effect of the combination of POC concentration, rice washing water and planting distance on the growth and yield of mung bean plants (Vigna radiata L.) of the Vima 1 cultivar. The research was carried out in the Kedung Dadap block, Serang Village, Palimanan District, Cirebon Regency from May 2024 to August 2024. The experimental method used was using an experimental method with a group random design (RAK), consisting of 9 treatment combinations that were repeated 3 times. Data analysis was carried out using various fingerprints and further tests with the Duncan Brganda Distance Test at the level of 5%. The results showed that there was a real influence between the POC concentration of rice washing water and planting distance on the variables of plant height, number of leaves, flowering age, total number of pods, weight of dry seeds per plant, and weight of dry seeds per plot. The POC concentration of 50 ml/l rice washing water with a planting distance of 20 cm x 30 cm had the best effect on the weight of dry seeds per plot which resulted in a production of 1.65 kg/plot or equivalent to 1.83 tons/ha.